Natural to anthropogenic influence of environmental change of Jakarta Bay: seismic reflection and sediment coring studies - Permana, Haryadi; Hananto, Nugroho Dwi; Zuraida, Rina; Susilohadi, Susilohadi; Suryoko, Mustaba Ari; Nazarudin, Nazar; Saputro, Eko; Sinaga, Adi C; Nugroho, Septriono Hari (Indonesian Journal of Geospatial, 2015)
Abstract. The shallow of high resolution seismic reflection profiles recorded dynamic development of Jakarta Bay. The interpretation results suggest least four transgression events and three events of regression. The last regression event characterized by rough erosional surface, deep and wide channel of fluvial or shallow marine environment. This event indicates strong energy sedimentation accompanied by high density material flow like as laharic flows or dense and frequent wet season. Upper part of seismic profile characterized by continues, parallel and thin sedimentation layer indicates gradual sea transgression event. The shallow sediment coring data, 100 cm to 160 cm length, indicates significant anthropogenic influences. At the depth 50 cm, the sediment core shows decreasing sharply of Si, Ca, Ti and Fe content interpreted as decreasing of volcanic source rocks. While to the near sediment surface was indicated by increasing of major element content such as Cu, Ti and Fe and also the heavy metals content such as Pb, Cr, Cd, Sn and Zn. The presence of major or heavy metals were possible related to human activities such as deforestation, industry, transportation and agriculture while in depth, the heavy metal content related to volcanic rocks as source rocks The environmental degradation in modern period detected at the sediment surface indicated by increasing sharply of Ammonia. Keywords : Shallow Sediment, Seismic Reflection, Antropogic Influence